RETORIKA VISUAL AKTIVISME DI INSTAGRAM: SISTEMATIK LITERATUR TENTANG AGENDA SETTING VISUAL DAN DAMPAKNYA TERHADAP KESADARAN POLITIK AUDIENS - Diva Ananda Alifia; Putri Nabila; Yuni Awaliyah; Yusuf Ali; Muhammad Isa Asyrofuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Instagram has transformed from a lifestyle platform into a crucial arena for political contestation, particularly in grassroots social movements such as the '17+8 People's Demands' Movement. This study aims to analyze how digital activism on Instagram facilitates political participation and shapes public agendas through visual rhetorical strategies. Employing a qualitative descriptive method with a library research approach, this study integrates Agenda Setting Theory, Connective Action concepts, and Visual Rhetoric. The results indicate that Instagram facilitates connective action through sharing mechanisms that are personal yet massively connected. Visually, the use of infographics and carousel aesthetics functions to frame complex issues into digestible narratives, thereby succeeding in intermedia agenda setting by moving issues from social media to mainstream public discourse. Findings also suggest that while visuals enhance political awareness, there is a risk of deep issue simplification. The novelty of this study lies in the specific analysis of the role of Instagram's visual instruments as the primary variable in shaping protest agendas in Indonesia. Keywords: Digital Activism, Connective Action, Instagram, Political Participation, Visual Rhetoric.